THU0498 Increase of CXCR3-CCR4+CCR6+CCR10- Memory T Helper Cells (TH17-LIKE) in Patients with Granulomatosis and Polyangiitis (GPA). (10th June 2014) - Jakiela, B.; Wawrzycka, K.; Szczeklik, W.; Hubalewska-Mazgaj, M.; Surmiak, M.; Sanak, M.; Musial, J.
Abstract : Background: Granulomatosis and polyangiitis (GPA) is a systemic vasculitis associated with anti-proteinase-3 antibodies and T-cell activation. Recruitment of memory T-cells into inflammatory sites depends on chemokine receptors and their specific patterns shape functional properties (e.g. cytokine production) of T helper-cells. Methods: We analyzed subtypes of peripheral blood CD4+ memory (CD45RA-) T-cells identified by the expression of CCR7, CXCR3, CCR4, CCR6 and CCR10 chemokine receptors (multicolor flow cytometry) in GPA patients (n=20, 3 with active disease) and age matched healthy controls (n=18). Results: GPA patients showed decreased percentage of CD4+ naïve cells (mean 20, 8 vs. 44, 4% in controls) and increased fraction of CD45RA-CCR7- effector memory cells (33, 8 vs. 19, 2%). A significant increase in the percentage of CXCR3+, CCR4+ and CCR6+ (but not CCR10+) CD4+ cells was also observed. When analyzing co-expression of chemokine receptors, we were able to identify 16 different subpopulations of CD4+ memory T-cells, with only CCR6+ subtypes elevated in GPA. Of note, in GPA we found significant increase in the frequency of CXCR3+CCR4-CCR6+CCR10- CD4+ cells (Th1Th17-like, 13, 6 vs. 9, 7% in controls) and CXCR3-CCR4+CCR6+CCR10- CD4+ cells (Th17-like, 11, 2 vs. 6, 4% in controls). The latter subtype was also significantly elevated in analysis limited to CD45RA- cells. Differences in CCR6+ fraction were most evident in patients with lung involvement and in those treated with low dose GCS (<4 mg/d or steroid-free). However, they were not related to additional immunosuppressive treatment (e.g. AZA or MTX) or disease activity. Conclusions: We show that CD4+ cells in GPA patients are switched towards effector memory phenotype, possibly as a signature of disease-related immune activation. We also found expanded CCR6+CCR10- subsets suggesting the involvement of Th1Th17-like and Th17-like cells in the pathogenesis of the disease. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3614